H+/K+ATPase Expression in the Larynx of Laryngopharyngeal Reflux and Laryngeal Cancer Patients. (6th April 2020) - McCormick, Caroline A.; Samuels, Tina L.; Battle, Michele A.; Frolkis, Talia; Blumin, Joel H.; Bock, Jonathan M.; Wells, Clive; Yan, Ke; Altman, Kenneth W.; Johnston, Nikki
Abstract : Objectives: The gastric H+/K+ ATPase proton pump has previously been shown to be expressed in the human larynx, however its contribution to laryngopharyngeal reflux (LPR) signs, symptoms and associated diseases such as laryngeal cancer is unknown. Proton pump expression in the larynx of patients with LPR and laryngeal cancer was investigated herein. A human hypopharyngeal cell line expressing the proton pump was generated to investigate its effects. Study Design: In‐vitro translational. Methods: Laryngeal biopsies were obtained from three LPR and eight LSCC patients. ATP4A, ATP4B and HRPT1 were assayed via qPCR. Human hypopharyngeal FaDu cell lines stably expressing proton pump were created using lentiviral transduction and examined via transmission electron microscopy and qPCR for genes associated with inflammation or laryngeal cancer. Results: Expression of ATP4A and ATP4B was detected in 3/3 LPR, 4/8 LSCC‐tumor and 3/8 LSCC‐adjacent specimens. Expression of ATP4A and ATP4B in FaDu elicited mitochondrial damage and expression of IL1B, PTGS2, and TNFA ( P < .0001); expression of ATP4B alone did not. Conclusions: Gastric proton pump subunits are expressed in the larynx of LPR and LSCC patients. Mitochondrial damage and changes in gene expression observed in cells expressing the full proton pump, absent in those expressing a single subunit, suggest that acid secretion by functional proton pumps expressed in upper airway mucosa may elicit local cell and molecular changes associated with inflammation and cancer. Level of Evidence: NA Laryngoscope, 131:130–135, 2021